Expression pattern and ligand‐binding properties of odorant‐binding protein 13 from Monochamus alternatus hope. (18th February 2017) - Li, N.; Sun, X.; Wang, M.‐Q.
Abstract: Odorant‐binding proteins (OBPs) are believed to play an important role in olfactory recognition. In this study, expression pattern and fluorescence binding characteristics of MaltOBP13 from the Japanese pine sawyer beetle, Monochamus alternatus Hope, were investigated via qPCR analysis of MaltOBP13 mRNA level and binding assay of MaltOBP13 and ligands. qPCR monitoring indicated MaltOBP13 mainly expressed in newly emerged males, particularly highly expressed in the last abdominal segment of males, and the expression level was significantly higher in 13‐day‐old mated adults than those of other stages. To further understand the function of the MaltOBP13 protein in odorant reception, the binding affinity of recombinant MaltOBP13 to ligands was tested by fluorescence binding assays with N ‐phenyl‐1‐naphthylamine as a fluorescent probe. The results of this assay indicated that MaltOBP13 exhibited a high binding affinity for pine volatiles and binding capacity was higher in acidic conditions than in neutral environment, indicating a possible role in finding host plants.